The Significance of Rhizobacteria for Strawberry Cultivation in Tropical Area: A Review - Febby Fitriyani; Etty Pratiwi; Masako Akutsu; Reginawanti Hindersah; Syariful Mubarok (Tropical Life Sciences Research, 2025)
In tropical regions, high temperatures and low nitrogen (N) and phosphorus (P) in soil limit plant performance and fruit production. The soil-beneficial microbes, including rhizobacteria, have the potential to overcome the nutrient problems in the soil. Rhizobacteria fix the dinitrogen, solubilise the P and potassium (K), and produce hormones and other metabolites to stimulate plant development and resistance against environmental challenges like inadequate soil fertility, heavy metal concentrations or drought. Bacterial genera that occur for promoting growth is Bacillus sp., Azospirillum sp., Azotobacter sp, Pantoea sp. and Pseudomonas sp. Despite the prominent role of rhizobacteria in agriculture and the economic value of strawberries, the potential use of rhizobacteria as a biofertiliser in strawberry cultivation in tropical areas is rarely discussed and reviewed. The information obtained from publications from 2014–2023 by using the keywords of Plant Growth Promoting Rhizobacteria (PGPR), tropics, biofertiliser, N fixation, P and K solubilisation, P mineralisation, phytohormones and strawberry is organised according to the rhizobacteria, mechanisms by which they boost plant growth, and research location in tropical area. This review focuses on evaluating (i) the mechanism of rhizobacteria to increase plant growth, (ii) the role of rhizobacteria on strawberry growth, yield and quality and (iii) the impact of rhizobacteria on biotic and abiotic stress alleviation.